Analysis of invariant spanning curves in oval billiards: A numerical approach based on Slater’s theorem - Hermes, Joelson D. V. (2025)
The study of billiards investigates the trajectories of particles that move freely in a region and reflect elastically at boundaries. Although there is already considerable understanding about invariant spanning curves, also known as whispering gallery orbits in the context of billiards, their determination in the phase space of the system, in addition to the analysis of their existence is still an open question. Our proposal is to present a numerical method based on Slater’s theorem, capable of determining the location of these curves in phase space, as well as finding the critical parameter at which these curves are no longer observed. In this work, we apply this method to determine the location of a set of invariant spanning curves in an oval billiard for different parameter values. Furthermore, we identified the critical parameter at which the phase space no longer presents these curves and local chaos becomes global. We compared our numerical results with analytical results present in the literature, proving the effectiveness of the proposed method. By studying the rotation number, we obtain additional information about the behavior of these curves and also of the systems.